Total Quality Management (TQM) and environmental focus for competitive advantage in Malaysian telecommunication industry - Chong, Sze Thiam (2013)
An enormous amount of literature on Total Quality Management (TQM) and Environmental Focus (EF) pronounces that these management practices bring about business results such as customer satisfaction, financial performance and competitive advantage (CA), however, empirical researches dealing with the relationships among TQM, EF and CA are still scarce. Both TQM and EF efforts have generally created valuable contributions to companies which implemented them seriously. Many researchers have confirmed TQM and EF as potential sources for CA. Despite extensive researches in various industries and countries, the relationships among TQM, EF and CA are seldom, if not never, being studied in the Telecommunication Industry, especially in Malaysia. The study aims to find out the extent of TQM and EF adoption among Telecommunication companies in Malaysia, the extent to which TQM practices and EF result in a CA, and where should companies operating in the Telecommunication Industry concentrate efforts to achieve Customer Satisfaction and improved performance.